HARGA POKOK PRODUKSI DALAM MENENTUKAN HARGA JUAL WOODEN BOX DI PT PRATAMA MANDIRI PERKASA - Wulandari, Diana; Yando, Agus Defri (EDUTECH CONSULTANT, 2020)
The cost of the product is a fee incurred by the company to avoid raw material. In this study aims to know the calculation of the price of production with full costing method in specifying the price of Juali wooden box in PT Pratama Mandiri Perkasa. Using the interior Costing method has a higher nominal value compared to the methods that the company uses. This research uses a descriptive research method, because its implementation includes data, analysis and interpretation of data meaning obtained, one of the techniques for collecting data is the and observation techniques (observation) and documentation. The results of this research show that there is a difference in the price calculation of the production of full costing method and with the method that the company use the difference is quite relevant so that it can affect the accuracy of the sale price In January 2018 the main price of the company's production was Rp. 60,056,412 and Rp. 71,265,444 for full costing method, and has selishi amounting to Rp. 11,209,032. For the selling price in January 2018, namely Rp. 2,400,000 and Rp. 2,740,000 using full method costing.